The role of the teacher in developing awareness of environmental risks among primary school students in Makkah Al-Mukarramah in light of the cognitive learning theory - Alotaibi, Mukhlid Saad (Journal of Curriculum and Teaching Methodology, 2025)
This study aimed to identify the role of teachers in enhancing environmental risk awareness among elementary students in Mecca, based on cognitive learning theory, and to explore the presence of statistically significant differences in the sample responses based on demographic variables such as age, gender, and experience, as well as to determine the requirements for activating this role. The study employed a descriptive survey method to examine the phenomenon as it exists and to gather and analyze the necessary data. The study sample included 473 male and female elementary teachers, with a questionnaire used as the data collection tool. Results indicated that the average role of teachers in fostering environmental awareness among students was high, with statistically significant differences favoring female teachers, while no significant differences were observed based on age or teaching experience. The study recommended enhancing environmental curricula by incorporating more environmental topics in alignment with Vision 2030 and developing training programs for teachers to update their knowledge and tools in environmental education.